ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NON MUSLIM MENJADI NASABAH BANK SYARIAH MANDIRI DI MEDAN - Evi Yupitri; Raina Linda Sari (Ekonomi dan Keuangan, 2012)
The purpose of this study is to see how big the influence of facilities, promotions and products affect the non muslim community to become a customer Bank Syariah Mandiri. The data used in this research is the primary data is obtained from the division of  a detailed questionnaire to the customer self service rich Islamic Bank on Jl. Jend Achmad Yani no.100 Medan. Sampling method used by researchers is a non probability sampling is a technique where each member of the sample on the take the population has  the same opportunity to become a member of sampling. Sample technique uptake of engineering purposive sampling ( Judgment Sampling ) is The sampling technique based on the assessment of the characteristics of sample members who adjusted with the goal of researchers. Data analysis method used is the rank spearmant test with SPSS 16 tools. Based on the results  factors that most strongly affects non Muslim become cust.omers in Bank Syariah Mandiri is a potent influence 0,370 promotions, both 0,529 products have potent influences and who was last 0,469 facilities had an influence that is.